Comparison of alternatives to amplitude thresholding for onset detection of acoustic emission signals - Bai, F.; Gagar, Daniel; Foote, Peter; Zhao, Yifan (Elsevier, 2016)
Acoustic Emission (AE) monitoring can be used to detect the presence of damage as well as determine its location in Structural Health Monitoring (SHM) applications. Information on the time difference of the signal generated by the damage event arriving at different sensors in an array is essential in performing localisation. Currently, this is determined using a fixed threshold which is particularly prone to errors when not set to optimal values. This paper presents three new methods for determining the onset of AE signals without the need for a predetermined threshold. The performance of the techniques is evaluated using AE signals generated during fatigue crack growth and compared to the established Akaike Information Criterion (AIC) and fixed threshold methods. It was found that the 1D location accuracy of the new methods was within the range of <1–7.1%<1–7.1% of the monitored region compared to 2.7% for the AIC method and a range of 1.8–9.4% for the conventional Fixed Threshold method at different threshold levels.
Keywords: Onset detection; Acoustic emission; Structural health monitoring